Additional Term Position of Constitutional Judges in The Perspective of Fiqh Priority of Yusuf Qardhawi - Fajrul Falah (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
Emergence of the third amendment to the law on the constitutional court which was passed suddenly has sparked controversy among experts. This is due to three irregularities in the law. Among them are the discussion of the law is considered very fast, changes regarding the addition of the term of office of constitutional judges and the very fullness of the law with indications of political interests in order to facilitate the interests of the proposing institution. In examining this problem, this research uses the theoretical perspective of the working of law from Chambliss and Seidman and fiqh siyasah from Yusuf Qardhawi. This research is a normative legal research and with a statute approach and conceptual approach. The findings in this study indicate that an increase in the tenure of constitutional judges who continue to use retirement is in line with Yusuf Qardhawi's priority fiqh theory for several reasons, including a form of harmonization in regulating the tenure of the highest holder of judicial power and being able to maintain independence and credibility of every constitutional judge's decision.